2018
DOI: 10.1002/hyp.13141
|View full text |Cite
|
Sign up to set email alerts
|

The role of urban growth, climate change, and their interplay in altering runoff extremes

Abstract: Changes in climate and urban growth are the most influential factors affecting hydrological characteristics in urban and extra‐urban contexts. The assessment of the impacts of these changes on the extreme rainfall–runoff events may have important implications on urban and extra‐urban management policies against severe events, such as floods, and on the design of hydraulic infrastructures. Understanding the effects of the interaction between climate change and urban growth on the generation of runoff extremes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 77 publications
(125 reference statements)
1
31
1
Order By: Relevance
“…The trigger factors of flooding disaster impacts are not only natural, such as extreme rainfall events, high floods, and high tides, but also anthropogenic, such as land use change (LUC), deforestation in upstream regions, and urbanization [1]. Climate change and urbanization are among the various factors that contribute to increased flood disaster risks which hinder the current and future urban flood management strategies [2][3][4][5][6]. Climate change is expected to change the hydrological cycle, prompting a greater likelihood of an extreme climate, including floods and dry seasons [7].…”
Section: Introductionmentioning
confidence: 99%
“…The trigger factors of flooding disaster impacts are not only natural, such as extreme rainfall events, high floods, and high tides, but also anthropogenic, such as land use change (LUC), deforestation in upstream regions, and urbanization [1]. Climate change and urbanization are among the various factors that contribute to increased flood disaster risks which hinder the current and future urban flood management strategies [2][3][4][5][6]. Climate change is expected to change the hydrological cycle, prompting a greater likelihood of an extreme climate, including floods and dry seasons [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, Pumo et al [23] showed the interaction between climate and land use and identified the fundamental hydrological dynamics through hydrological modeling. Especially, Arnone [24] identified the effects of climate change on urban growth by the simulation of a physically based distributed hydrological model. Therefore, hydrological modeling could become an effective tool to identify natural factors and anthropogenic factors if it was well developed and calibrated.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the availability of higher resolution spatio-temporal datasets, the appearance of high performance computers, and the development of parallel-computing [2][3][4][5] have opened the possibility of using these models for large size basins and long-term hydrological continuous simulations. Thus, challenges such as the influence of land-use changes [6,7] or the impact of climate change [8,9] on the involved hydrological processes can be analyzed with these approaches.…”
Section: Introductionmentioning
confidence: 99%